The development of dedicated CFD solver for aerodynamic analysis on internal and external flow - Alakashi, Abobaker Mohammed (2015)
There are various engineering applications which required one has to solve an internal or an external flow problem. The design of flying vehicles such as aircraft, helicopter, missiles are examples which the ability to solve an external flow problem will determine the success in designing such flying vehicles. While for the case of flows pass through intake of the engine, compressor, turbine and nozzles, the ability to deal with internal flow problem is needed. Basically the external and internal flow problems are governed by the same equation, their difference may come from their difference in term of their boundary conditions. If both flow problems are under high Reynolds number condition and involves with the flow problems pass through a streamline body at relatively a low angle of attack, the viscous effects can be ignored. However if the flow is belong to class of a flow above a high subsonic flow, the suitable governing equation of fluid motion is a compressible Euler equations. Unfortunately, such a kind governing equation of fluid motion cannot be solved analytically; a numerical approach is required for solving it. The present work focuses on the use of two types of Finite Volume methods. The first Finite volume method is a Cell-Centered Finite volume Scheme, while the second one is the Roe’s Finite Volume Scheme. In parallel to the development of computer code based on finite volume schemes, the present works also carry out work on solving the governing equation of fluid motion by use of Finite Difference Approach. In this respect the present work focuses on the use of Steger Warming Scheme and MacCormack Scheme are applied to Nozzle flow problems. To implement the Finite volume method as well as the Finite difference method in relating to the case of internal and external flow problems, the present work applies a combination of Algebraic grid generation and Elliptic Grid. In vi addition to this, the developed computer codes are designed in such away to allow one solve the flow problem by use of structured grid or unstructured grid. To validate the developed computer codes, their results compare with the result for the flow problem which the experimental results are available such as for the case airfoil NACA 0012. While for other test cases such the flow past rotor blades is compared with the result provided from solving the flow problem by use of Fluent software. Through comparison result with the Fluent software as well as the available experimental results indicate that the developed computer code are in a good agreement.